SOSIALISASI PENERAPAN PROTOKOL KESEHATAN DAN PEMBAGIAN PERALATAN CUCI TANGAN BAGI MASYARAKAT KAMPUNG SAMAU MENUJU MASYARAKAT SEHAT DI KABUPATEN BIAK NUMFOR PAPUA - Krismiyati Krismiyati; Rani Maswati; Salehudin Salehudin; Jelita Punamasari (Universitas YPPI Rembang, 2021)
This community service program was carried out in Samau Village, Biak City District, Biak Numfor Regency in partnership with the Kota Biak Community Health Center as one of the pilot Family Planning (KB) villages. The purpose of this socialization and distribution of tools is to increase community awareness about the implementation of health protocols in the vicinity of the environment where they live and in village public facilities and to provide the community with skills to make their own health protocols tools that the community will use themselves. Methods in the implementation of community service, namely the Socialization of health protocol by the TEAM, Puskemas Biak Kota and Students, and the practice of making medical devices. From the results of this 1 (one) month Community Service program are: 1) Implementation of 2 (two) health protocol implementation socialization activities and production of health protocol tools and distribution to the community in Samau village and spraying disinfectants in churches and schools of Aru Biak Elementary School. The result was an increase in the understanding of the community in Samau village of the importance of education. Health protocols and the community being able to make their own equipment.Keywords: Socialization, Health Protocols, Community of Kampung Samau